KOMUNIKACJA LEKARZ–PACJENT W PLACÓWKACH SŁUŻBY ZDROWIA - Drop, Katarzyna; Drop, Bartłomiej (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
It is very hard to clearly define the term of communication, because it relates to many notions and different fields of life. In this publication the authors tried to characterized it as a process of information changing between its participants – a sender and a receiver. Interpersonal communication is one of the specific forms of communication, in which doctor-patient communication is the most important in the field of medicine. Relation between mentioned participants is very crucial because the effects of the process of healing and getting better depends on how the doctor and the patient cooperate with each other. The best doctor seems to diagnose patient and prepare proper methods of treating as quick as possible. That type of person seems to be responsible for breaking the bad news to the patients, giving advice how to dose different medicines he/she prescribed, explaining the purpose of hospital admission and defining the adverse effects of specific medicines the patient has to take. The aim of this paper is to explain, define and describe the relation between doctor and patient in medical units. This is why the authors discussed such basic terms as: communication (scheme of communication), communication mistakes, barriers between doctor and patient, general rules about physician-patient relationships, patient rights, doctor-patient relationship. This publication is the first - theoretic part in which the authors precisely defined the terms mentioned above. The next part of this paper is the study, in which the results of survey will be shown. A group of Lublin medical units patients fill in the questionnaire and asked the questions about their observations of doctor-patient relationship. The next part will be the base to discuss and think how the mentioned relations should look like.